The Impact of Virtual Embeddedness on New Venture Survival: Overcoming the Liabilities of Newness - Morse, Eric A.; Fowler, Sally W.; Lawrence, Thomas B. (Entrepreneurship Theory and Practice, 2007)
In this article, we examine the impact of virtual embeddedness—the establishment of interorganizational connections through the use of electronic technologies—on the likelihood of new venture survival. We explore the effects of recent technological and social changes on traditional conceptions of the liabilities of newness. We argue that virtual embeddedness positively affects new venture survival by decreasing the liabilities of newness associated with a new venture's need to create and manage new roles and systems, lack of extant trust relationships, lack of social capital, and lack of economic capital. This argument has important implications for both the study and management of contemporary new ventures.